PERSEPSI MAHASISWA TERHADAP NATIVE ENGLISH TEACHERS (NET) DALAM MATA KULIAH SPEAKING 1 DAN WRITING 1 - Feisal Aziez (Universitas Islam Nahdlatul Ulama Jepara, 2015)
This descriptive research aimed at exploring students?? perception and expectation on native English teacher (NET) in teaching and learning process in two subjects namely Speaking 1 and Writing 1 at the Department of English Language Education in Muhammadiyah University of Purwokerto. This study provides an insight and a basis for evaluation regarding the presence and contribution of the NET at the university. Furthermore, this study could as well become a reflection for professional development of both NET and Non-NET at the university. The data in this study was collected by using questionnaires and interview. Overall, 40 first-year-students who took the aforementioned subjects participated in this research. This research reveals that, in general, the current NET has met the expectations of the students. However, the students believe that the number of the NET at the university is insufficient and they also believe that the current NET doesn??t give them enough assignment